CDK5 interacts with Slo and affects its surface expression and kinetics through direct phosphorylation - Bai, Jun-Ping (American Physiological Society, 2012)
Large-conductance calcium-activated potassium (BK) channels are ubiquitous and play an important role in a number of diseases. In hair cells of the ear, they play a critical role in electrical tuning, a mechanism of frequency discrimination. These channels show variable kinetics and expression along the tonotopic axis. Although the molecular underpinnings to its function in hair cells are poorly understood, it is established that BK channels consist of a pore-forming α-subunit (Slo) and a number of accessory subunits. Here we identify CDK5, a member of the cyclin-dependent kinase family, as an interacting partner of Slo. We show CDK5 to be present in hair cells and expressed in high concentrations in the cuticular plate and in the circumferential zone. In human embryonic kidney cells, we show that CDK5 inhibits surface expression of Slo by direct phosphorylation of Slo. Similarly, we note that CDK5 affects Slo voltage activation and deactivation kinetics, by a direct phosphorylation of T847. Taken together with its increasing expression along the tonotopic axis, these data suggest that CDK5 likely plays a critical role in electrical tuning and surface expression of Slo in hair cells.